Improvement in the signs and symptoms of dry eye disease with dobesilate eye drops. Issue 1 (December 2015) - Cuevas, Pedro; Outeiriño, Luis; Azanza, Carlos; Angulo, Javier; Giménez-Gallego, Guillermo
Abstract Background Dry eye is a multifactor disease of the tear film and ocular surface that substantially affects quality of life. Case presentation Dobesilate administered as eye drops was well tolerated and effective in treating both the objective signs and subjective symptoms of dry eye disease in this 2-week study. Conclusion To the best of our knowledge, this is the first clinical report of using dobesilate in eye drops. Dobesilate may provide a novel approach to treating drying diseases of the eye.